The Influence of Management Control and Leadership Style on Good Corporate Governance with Organizational Commitment as a Mediating Variable (Empirical Study at PT Paraduta Servis Indonesia) - Usrial, Nur Muhammad Majid; Sulhendri, Sulhendri (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to determine the effect of management control and leadership style on good corporate governance, with organizational commitment as a mediating variable. Data collection methods used Google Forms, and the study population consisted of 220 employees of PT Paraduta Servis Indonesia. Data analysis used Structural Equation Modeling. (SEM), validity test, reliability test, and hypothesis test. In this study, the validity test of all scales is declared valid, this is because the factor loading value (in the Original sample column) is more than 0.5 and the probability value (P values) is below 0.05. The variable reliability test is also declared reliable because the value of each variable is above the minimum value of 0.70. The hypothesis test of this study shows that management control has a significant effect on Good Corporate Governance (GCG), leadership style has a significant effect on Good Corporate Governance (GCG), organizational commitment has a significant effect on Good Corporate Governance (GCG), this can be seen from the P values less than 0.05, so the hypothesis is accepted. Management control through organizational commitment has a significant effect on Good Corporate Governance (GCG), leadership style through organizational commitment has a significant effect on Good Corporate Governance (GCG). This can be seen from the P Value is less than 0.05, so the hypothesis is accepted.